(untitled) (International relations and international law Journal, 2016)
The article deals with the problematic issues of the scientific definition of the notion and the essence of the subject of forensic examination. In this regard the author analyzes the views of scientists-criminalists and lawyers-practitioners who have researched the aspect of expertise knowledge and expressed controversial opinions on the subject of the forensic examination as a practical activity. Referring to the critical analysis of the suggested scientific definitions given in special literature, the difference between such notions as «subject», «tasks», «questions» and «objects» has been considered in the article. Besides, the author expresses his vision on the solution of theoretical questions in the course of analyzing the problem under consideration, which is of great practical significance from the point of its substantiated application in the judicial process of the notional apparatus of the forensic expertise.